Особливості існуючих вебзастосунків для розпізнавання та контролювання правильності виконання фізичних вправ - Голубович, Є. Д. (ХНУРЕ, 2025)
This work is devoted to analyzing and developing an accessible and convenient tool for personal training, which uses and combines the latest technologies for advanced control of physical activity. The relevance of the task in the modern world is described. The web application, the development of which is described in this work, is designed to solve this problem by using computer vision methods to analyze keypoints of the body during exercise. This will allow users to inde-pendently control the quality of their training in real time without the constant presence of a trainer.
Keywords: фізична вправа; виконання фізичних вправ